Sea surface temperature trends and the influence of ENSO on the southwest sea of Vietnam using remote sensing data and GIS - Tuan, Tran Anh; Dang, Vu Hai; Hong, Pham Viet; Thuc, Do Ngoc; Linh, Nguyen Thuy; Nguyet, Nguyen Thi Anh; Hien, Pham Thu; Phuong, Vu Le (Vietnam Journal of Marine Science and Technology, 2020)
In this article, the sea surface temperature trends and the influence of ENSO on the southwest sea of Vietnam were analyzed using the continuous satellite-acquired data sequence of SST in the period of 2002–2018. GIS and average statistical methods were applied to calculate the average monthly and seasonal sea surface temperature, the seasonal sea surface temperature anomalies for each year and for the whole study period. Subsequently, the changing trends of sea surface temperature in the northeast and southwest monsoon seasons were estimated using linear regression analysis. Research results indicated that the sea surface temperature changed significantly throughout the calendar year, in which the maximum and minimum sea surface temperature are 31oC in May and 26oC in January respectively. Sea surface temperature trends range from 0oC/year to 0.05oC/year during the Northeast monsoon season and from 0.025oC/year to 0.055oC/year during the southwest monsoon season. Results based on the Oceanic Niño Index (ONI) analysis also show that the sea surface temperature in the study area and adjacent areas is strongly influenced and significantly fluctuates during El Niño and La Niña episodes.